(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2018)
Dacope Upazilla under Khulna district is one of the most affected safe water scarcity regions like any other part of southwest coastal region of Bangladesh. The demands for drinking and cooking water in the area are mostly met from rainwater harvesting and pond water. Pond water from different stations of Dacope Upazilla was analyzed for assessing the water chemistry, source rock evaluation and its potability status. Thirty one samples were collected by purposive sampling and analyzed following standard methods. The analysis reveals that the cations and anions of the ground water showed the order of abundance as Na+> Mg++>Ca++>K+ and Cl->SO4 –>HCO3 - , respectively. Source rock deduction suggests that the water is mostly carbonate weathering of sea water or brine intrusion. Piper diagram suggests that the water is in saline condition. Ionic ratios also justify the aforesaid relations. The chemical constituent of water is (Na++K+) and (Cl- +HCO3 -) type influenced by sea water, however, ponds are in transition zone influenced by tide. With reference to Bangladesh and WHO standards the research states that most pond water do not satisfy the potable quality, therefore management options need to be formulated for further exploitation. Asiat. Soc. Bangladesh, Sci. 44(2): 159-171, December 2018